High-Q-value harmonic oscillator based on novel SrTiO3-LaAlO3-based microwave dielectric ceramic material and preparation method of high-Q-value harmonic oscillator

By adding Ca, Ce, Ga and other elements to SrTiO3-LaAlO3 microwave dielectric ceramics, the problems of high-temperature oxygen loss and black center phenomena during sintering are solved, and the preparation of high-quality oscillators at lower sintering temperatures is achieved, which is suitable for industrial production.

CN119751052AActive Publication Date: 2025-04-04UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411921714.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing SrTiO3-LaAlO3 microwave dielectric ceramics have high temperature oxygen loss and black centering phenomena during the sintering process, resulting in a decrease in dielectric performance and a high sintering temperature, which limits its application.

Method used

By adding elements such as Ca, Ce, Ga, etc. to SrTiO3-LaAlO3-based ceramics, their chemical composition is adjusted, the sintering temperature is reduced, and sintering is achieved in the air, and the defects in the high-temperature sintering process are overcome.

Benefits of technology

It is realized that the oscillators with high quality factor (Q×f) and excellent microwave dielectric properties are prepared at a lower sintering temperature (1500℃~1600℃), and the process is simple and stable, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751052A_ABST
    Figure CN119751052A_ABST
Patent Text Reader

Abstract

The invention aims to provide a novel SrTiO3-LaAlO3-based microwave dielectric ceramic and a preparation process of a harmonic oscillator thereof, the chemical formula of the novel SrTiO3-LaAlO3-based microwave dielectric ceramic is Sr (y-z) CazTi1-mCemO3-xLa1-nGanAlO3, x is more than or equal to 0.7 and less than or equal to 1.15, y is more than or equal to 0.98 and less than or equal to 1.01, and z is more than or equal to 0.05 and less than or equal to 0.15; 0.001 < = m < = 0.01; 0.001 < = n < = 0.015; the sintering temperature in the air is 1500-1600 DEG C, the resonant frequency is 2.4-2.6 Ghz, the Q value is 17700-19800, and the temperature coefficient of resonance frequency is 0 + / -5 ppm / DEG C. The sintering condition of the harmonic oscillator is simple, the sintering atmosphere is air, the performance is greatly improved, the performance is stable, the application requirement of the modern communication technology can be met, and the harmonic oscillator can be widely applied to preparation of microwave components such as microwave dielectric resonators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic information functional materials, and relates to a method for preparing a microwave dielectric ceramic material and a resonator, and specifically to high quality factor microwave communication components such as dielectric resonators and dielectric filters that can be used to manufacture modern communication technologies. Background Art

[0002] The frequencies used in microwave communication technology are mainly between 300MHz and 300GHz, and it has the characteristics of high frequency, wide bandwidth, large information capacity, and multi-channel communication. Microwave dielectric resonators play a vital role in the field of microwave communication due to their small size, light weight, high dielectric constant and Q value, and good temperature stability. Dielectric resonators are the most basic microwave components. Dielectric resonators can be used to form microwave circuits such as filters, oscillators, and antennas, which help to achieve miniaturization and high frequency of microwave circuits and systems. Its development in circuit applications is related to the urgent requirements of the development of space and military electronic technology for the miniaturization, integration, and high reliability of microwave circuits. With the rapid development of 5G communication technology, the requirements for microwave communication devices have become more stringent, which also means that the preparation of resonators with excellent performance requires more excellent underlying materials for microwave communication technology. Traditional metal devices cannot meet the performance requirements of the new generation of communication systems due to weight and volume limitations. Therefore, microwave dielectric ceramics have attracted much attention as a key material. Microwave dielectric ceramics have excellent properties such as low dielectric loss, high quality factor and stable resonant frequency temperature coefficient, which directly affect the performance of microwave resonators prepared using them.

[0003] (1-x)MTiO3-xLnAlO3 (M=Ba, Sr, Ca;Ln=La, Nd, Sm, etc.) series microwave dielectric ceramics are a type of composite ceramics with a perovskite solid solution structure. MTiO3-LnAlO3 has the advantages of low dielectric loss, adjustable dielectric constant and good microwave performance. Its dielectric constant and dielectric loss can meet research needs and are widely used in military radar, mobile communication base stations and Ku-band digital TV receiving systems. SrTiO3-LaAlO3-based ceramics are a promising microwave dielectric ceramic. They have been widely studied because of their excellent dielectric properties. When the ratio of SrTiO3 to LaAlO3 reaches a certain value, its dielectric constant is ε r =40, Q×f≥40000GHz, frequency temperature coefficient τ f=0±5ppm / ℃. However, pure SrTiO3-LaAlO3 has a relatively low application value due to its high sintering temperature (>1650℃) and the black core phenomenon caused by high-temperature oxygen loss during the sintering process, which greatly deteriorates its dielectric properties. The research on SrTiO3-LaAlO3 microwave dielectric ceramics began in the 1990s. Sun PH, Nakamura T et al. reported the performance of SrTiO3-LaAlO3 ceramics in the article "Dielectric behavior of (1-x) SrTiO3-xLaAlO3 solid solution system at microwave frequencies" in the Japanese Journal of Applied Physics in 1998. In 1999, Seo-Yong Cho et al. reported in the paper "Mixture-like behavior in the microwave dielectric properties of the (1-x)SrTiO3-xLaAlO3 system" in Materials Research Bulletin that the dielectric properties of ceramics were obtained by synthesizing SrTiO3 and LaAlO3 powders separately and then mixing and sintering them in a certain proportion. In 2001, Huang CL et al. published a study titled "Improved high Q value of 0.5LaA1O3-0.5SrTiO3 microwave dielectric ceramics at low sintering" in Materials Research Bulletin. When 0.25%-1%wt of B2O3 was added, the sintering temperature of 0.5LaA1O3-0.5SrTiO3 ceramics was reduced to 1430℃, but the large amount of glass phase added led to the deterioration of microwave performance. In the following years, a large number of researchers conducted research on SrTiO3-LaAlO3 series ceramics, and their research mainly focused on the phase change mechanism of ceramics during the composite process and the reduction of sintering temperature by doping CuO.In 2009, T. Shimada et al. reported an article titled "Effect of Sintering Atmosphere on Dielectric Properties of SrTiO3-LaAlO3 System" in Ferroelectrics. They sintered ceramics at different O2 partial pressures and found that as the proportion of SrTiO3 increased, the dielectric loss of SrTiO3-LaAlO3 ceramics increased; when the oxygen content in the sintering atmosphere increased, its dielectric loss decreased. XPS analysis showed that the reason was the semiconductorization of SrTiO3-LaAlO3 ceramics at high temperatures, and the mechanism was Ti. 4+ →Ti 3+ , which produces oxygen vacancies and causes the performance of microwave dielectric ceramics to deteriorate. Ceramics with high-quality microwave dielectric properties can be obtained by sintering in an O2 atmosphere, but the conditions required increase the requirements for sintering equipment and require higher sintering temperatures, which makes the promotion of practical ceramics face great resistance. In 2015, Zhang et al. published an article titled "(1-x)LaAlO3-xCa 0.2 Sr 0.8 Investigation on microwave dielectric properties and microstructures of (1-x)LaAlO3-xCa 0.2 Sr 0.8 TiO3 ceramics) reported (1-x)LaAlO3-xCa 0.2 Sr 0.8 The structure, microstructure and microwave dielectric properties of TiO3 ceramics confirm the formation of solid solution. Its lattice parameters, average grain size and dielectric constant (ε r )With Ca 0.2 Sr 0.8 The quality factor (Q×f) of TiO3 increases with the increase of TiO3 dosage, while the quality factor (Q×f) decreases. 3+ Effect of Substitution on Microwave Dielectric Properties of 0.67CaTiO3-0.33LaAlO3 Ceramics 3+substitution on the microwave dielectric properties of 0.67CaTiO3–0.33LaAlO3 ceramics), Dou et al. prepared 0.67CaTiO3-0.33La(Al 1-x Ga x )O3(0 < x < 0.4)(CTLAG) pure perovskite-structured ceramics and studied the effect of Ga 3+ substitution for Al 3+ on the microwave dielectric properties of the ceramics. The article found that with the increase in Ga content, the ionic polarizability of the ceramics increased, resulting in an increase in the dielectric constant (ε r ). At the same time, with the increase in Ga content, both the tolerance factor (t) and the A-site bond valence of CTLAG ceramics were considered to have an impact on the temperature coefficient of the resonant frequency (τ f ). The results also showed that the quality factor (Q×f) increased with Ga 3+The content of CaO / SnO2 varies with the increase of the content, which is due not only to intrinsic factors but also to extrinsic factors such as bimodal grain size distribution, changes in relative density and filler fraction. In 2017, Huang et al. reported in Ceramics International the effects of CaO / SnO2 additives on the sintering properties, phase composition, microstructure and dielectric properties of 0.6SrTiO3-0.4LaAlO3 (6ST-4LA) microwave dielectric ceramics prepared by conventional solid-state reaction method. The results showed that CaO / SnO2 as an additive had no obvious effect on the phase composition of 6ST-4LA ceramics, and all samples showed a pure ABO3 peroxide structure. The addition of an appropriate amount of CaO / SnO2 not only effectively reduced the sintering temperature from 1550℃ to 1400℃, but also improved the dielectric properties due to the formation of peroxide solid solution, and reduced microstructural defects and intrinsic losses. In 2022, Huang et al. reported the article "Effect of Si / Mg mole ratio on the phase transformation, sintering, and dielectric properties of 0.63SrTiO3-0.37LaAlO3 ceramics" in Journal of Materials Science: Materials in Electronics. They prepared 0.63SrTiO3-0.37LaAlO3 (63ST-37LA) ceramics by a solid-phase method and studied the effect of Si / Mg mole ratio on the phase transformation, sintering and dielectric properties of 63ST-37LA ceramics. When the molar ratio R=0.53 and the MgO addition amount is 2 mol%, at 1350°C, the dielectric properties of 63ST-37LA ceramics are significant, with a dielectric constant of 45.97, a Q center point f value of 69928 GHz, and a frequency temperature coefficient of 1.7 ppm / °C.In 2022, Luo et al. reported an article in Ceramics International titled "Effects of Y2O3 doping on the dielectric properties and microstructures of SrTiO3–LaAlO3 microwave dielectric ceramics". The article used conventional solid-phase reaction method to prepare Y2O3-doped SrTiO3-LaAlO3 (ST-LA) microwave dielectric ceramics. X-ray energy spectrum analysis showed that Y. 3+ The Y2O3 doping amount significantly affects the dielectric properties of ST-LA ceramics at microwave frequencies. 0.55SrTiO3-0.45LaAlO3 ceramics doped with 0.3wt% Y2O3 have excellent microwave dielectric properties, ε r =44.01, Q×f=59065GHz(5.966GHz) and τ f =6.09ppm / ℃.

[0004] In summary, based on SrTiO3-LaAlO3-based ceramics, by overcoming the black core formed during the sintering process, a new type of microwave dielectric ceramic with a high quality factor (high Q×f value) is studied, which can be sintered at medium temperature in air (<1600℃), has low raw material cost and good process repeatability. The dielectric ceramic is used to prepare a high-quality factor resonator, which has great scientific research value and market prospects and has the potential to be applied to new high-performance resonators. Summary of the invention

[0005] The purpose of the present invention is to provide a novel SrTiO3-LaAlO3-based microwave dielectric ceramic and a preparation and production process of a resonator thereof. The resonator made of the microwave dielectric ceramic has a dielectric constant close to 40, a relatively high Q value, a low frequency temperature coefficient, and a sintering temperature of less than 1600°C. It has high stability and is easy for industrial production. It can be widely used in the preparation of microwave components such as microwave dielectric resonators.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A new type of SrTiO3-LaAlO3 based microwave dielectric ceramic. Its chemical formula is

[0008] Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Gan AlO3, wherein 0.70≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; in the above microwave dielectric ceramic material, the role of Ca replacing Sr is to reduce the sintering temperature and adjust the temperature coefficient; the role of Ce replacing Ti is to reduce the reduction of tetravalent titanium in the ceramic and improve the microwave dielectric properties; the role of Ga replacing La is to overcome the defects generated during its high-temperature sintering process, thereby improving the microwave dielectric properties; the addition of the above elements to SrTiO3-LaAlO3-based microwave dielectric ceramics enables it to be sintered in air and adjust the microwave dielectric properties.

[0009] The present invention also provides a resonator based on a novel SrTiO3-LaAlO3-based microwave dielectric ceramic. The resonator is a microwave dielectric ceramic, and its chemical formula is Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n AlO3, wherein 0.70≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; the sintering temperature in air is 1500℃~1600℃, the resonant frequency is 2.4~2.6Ghz, the Q value is 17700~19800, and the resonant frequency temperature coefficient is 0±5ppm / ℃.

[0010] In addition, the present invention also provides a method for preparing a resonator based on a novel SrTiO3-LaAlO3-based microwave dielectric ceramic, comprising the following steps:

[0011] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, and prepare them according to the chemical formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material, wherein 0.70≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; the purity of each raw material is preferably more than 99.5%.

[0012] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0013] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1300° C. to 1500° C. for 2 to 5 hours to obtain a pre-sintered powder.

[0014] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0015] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0016] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0017] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0018] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1500° C. to 1600° C. in an air atmosphere for 4 to 10 hours to obtain a final resonator device.

[0019] Compared with the prior art, the present invention has the following characteristics:

[0020] 1. The formula of the resonator does not contain volatile or heavy metal elements such as Pb and Cd, and is an environmentally friendly and pollution-free dielectric resonator.

[0021] 2. The sintering temperature of SrTiO3-LaAlO3 ceramics without doping elements is greater than 1650°C, and the Q value of the resonator prepared using it is relatively low. The sintering temperature of this ceramic is between 1500°C and 1600°C. The Q value of the resonator using this dielectric ceramic is higher, and the preparation process has certain energy-saving advantages.

[0022] 3. The sintering conditions of the resonator are relatively simple, and the sintering atmosphere is air. The performance has been greatly improved, the performance is stable, and it can meet the application requirements of modern communication technology. It has great promotion and practical value and can be widely used in the preparation of microwave components such as microwave dielectric resonators.

[0023] 4. The raw materials are in sufficient supply and low price in China, which is suitable for the production of high-performance microwave communication components in modern communication technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD analysis result of the resonator prepared in Example 3 of the present invention.

[0025] Figure 2 This is a SEM image of the resonator prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] A new type of SrTiO3-LaAlO3 based microwave dielectric ceramic. Its chemical formula is

[0028] Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n AlO3, wherein 0.70≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; in the above microwave dielectric ceramic material, the role of Ca replacing Sr is to reduce the sintering temperature and adjust the temperature coefficient; the role of Ce replacing Ti is to reduce the reduction of tetravalent titanium in the ceramic and improve the microwave dielectric properties; the role of Ga replacing La is to overcome the defects generated during its high-temperature sintering process, thereby improving the microwave dielectric properties; the addition of the above elements to SrTiO3-LaAlO3-based microwave dielectric ceramics enables it to be sintered in air and adjust the microwave dielectric properties.

[0029] The resonator prepared using the above-mentioned microwave dielectric ceramic has a sintering temperature of 1500°C to 1600°C in air, a resonant frequency of 2.4 to 2.6 GHz, a Q value of 17000 to 19800, a resonant frequency temperature coefficient of 0±5ppm / °C, and a dense structure and good mechanical properties. Therefore, it can be used to prepare microwave components such as microwave dielectric resonators.

[0030] Example 1

[0031] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, and prepare them according to the chemical formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0032] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0033] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1300° C. for 3 hours to obtain pre-sintered powder.

[0034] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0035] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0036] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0037] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0038] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1500° C. in an air atmosphere for 9 hours to obtain a final resonator device.

[0039] Example 2

[0040] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0041] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0042] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1350° C. for 4 hours to obtain a pre-sintered powder.

[0043] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0044] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0045] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0046] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0047] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1550° C. in an air atmosphere for 6 hours to obtain a final resonator device.

[0048] Example 3

[0049] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, and prepare them according to the chemical formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0050] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0051] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1400° C. for 4 hours to obtain pre-sintered powder.

[0052] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0053] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0054] Step 6: Granulation. Add deionized water equivalent to 1 to 2 times the mass of the secondary ball-milled dried powder obtained in step 5, and 15% to 30% of the mass of the secondary ball-milled dried powder and a 5% to 7% concentration of polyvinyl alcohol solution, mix well, and then use a spray granulation device to spray granulate the obtained mixed slurry to obtain a dry powder.

[0055] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0056] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1570° C. in an air atmosphere for 7 hours to obtain a final resonator device.

[0057] Example 4

[0058] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, and prepare them according to the chemical formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0059] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0060] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1370° C. for 4.5 hours to obtain a pre-sintered powder.

[0061] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0062] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0063] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0064] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0065] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1530° C. in an air atmosphere for 6 hours to obtain a final resonator device.

[0066] Example 5

[0067] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0068] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0069] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1420° C. for 4.5 hours to obtain a pre-sintered powder.

[0070] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0071] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0072] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0073] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0074] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1600° C. in an air atmosphere for 5 hours to obtain a final resonator device.

[0075] Example 6

[0076] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0077] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0078] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1450° C. for 4 hours to obtain pre-sintered powder.

[0079] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0080] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0081] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0082] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0083] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1560° C. in an air atmosphere for 8 hours to obtain a final resonator device.

[0084] Example 7

[0085] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0086] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0087] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1470° C. for 3.5 hours to obtain a pre-sintered powder.

[0088] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0089] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0090] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0091] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0092] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1540° C. in an air atmosphere for 9 hours to obtain a final resonator device.

[0093] Example 8

[0094] Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials of SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material.

[0095] Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material.

[0096] Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1480° C. for 3 hours to obtain a pre-sintered powder.

[0097] Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles.

[0098] Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder.

[0099] Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder.

[0100] Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body.

[0101] Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1550° C. in an air atmosphere for 6 hours to obtain a final resonator device.

[0102] The microwave dielectric properties of the resonator samples obtained by the above experimental steps were tested by combining a network analyzer (Agilent Technologies E5071C) and a single-cavity test method to obtain the dielectric constants (ε r ), quality factor (Q), resonant frequency at 25°C (f 25 ), resonant frequency at 85°C (f 85 ). Based on the measured performance data, Q×f at 25°C is calculated. 25 value, the frequency drift (Δf) of the resonator at 85℃ and 25℃, and the frequency temperature coefficient (τ f ). The frequency temperature coefficient is given by the formula τ f =(f 85 -f 25 ) / (f 25 ×60) calculated.

[0103] The raw material composition and sintering process of preparing the resonator in Examples 1 to 8 are shown in Table 1:

[0104] Table 1 Specific formula and sintering process for preparing the resonator in Examples 1 to 8

[0105]

[0106] The microwave dielectric properties of the resonators prepared in Examples 1 to 8 are shown in Table 2:

[0107] Table 2 Microwave dielectric properties of the resonators prepared in Examples 1 to 8

[0108]

[0109] The most optimized solution in the embodiments is embodiment 3. The present invention is not limited to the above 8 specific embodiments. It should be noted that it is completely feasible to obtain a microwave dielectric ceramic resonator with excellent performance by properly adjusting the dopant and the preparation process, but this all falls within the scope of the present invention.

Claims

1. A new type of SrTiO3-LaAlO3 based microwave dielectric ceramic. Its chemical formula is Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1- n Ga n AlO3, wherein 0.7≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.

015.

2. A resonator based on a novel SrTiO3-LaAlO3-based microwave dielectric ceramic, characterized in that: The resonator uses microwave dielectric ceramics, and the chemical formula of the microwave dielectric ceramics is Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n AlO3, wherein 0.7≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; its sintering temperature in air is 1500℃~1600℃, the resonant frequency is 2.4~2.6Ghz, the Q value is 17700~19800, and the resonant frequency temperature coefficient is 0±5ppm / ℃.

3. A method for preparing a resonator based on a novel SrTiO3-LaAlO3-based microwave dielectric ceramic as claimed in claim 2, characterized in that The following steps are involved: Step 1: Ingredients. Take CeO2, Ga2O3, SrCO3, CaCO3, La2O3, Al2O3 and TiO2 as raw materials, according to the chemical composition formula Sr (y-z) Ca z Ti 1-m Ce m O3-xLa 1-n Ga n The raw materials SrCO3, CaCO3, La2O3, Al2O3 and TiO2 except CeO2 and Ga2O3 are mixed to obtain a mixed material, wherein 0.7≤x≤1.15, 0.98≤y≤1.01, 0.05≤z≤0.15; 0.001≤m≤0.01; 0.001≤n≤0.015; the purity of each raw material is preferably more than 99.5%. Step 2: primary ball milling. The mixed material prepared in step 1 is subjected to primary ball milling with deionized water and zirconium balls, the mass ratio of the mixed material, deionized water and zirconium balls being 1:1-2:1.5-2, the ball milling time being 5-10 hours, and after the ball milling, the ball milled material is dried at 110°C and passed through a 60-mesh sieve to obtain a primary ball milled material. Step 3: Pre-sintering: The primary ball mill obtained in step 2 is pre-sintered at 1300° C. to 1500° C. for 2 to 5 hours to obtain a pre-sintered powder. Step 4: Sieve. The powder obtained in step 3 is passed through a 60-mesh sieve to obtain a powder with fine particles. Step 5: Secondary ball milling. The sieved powder in step 4 is added to the weighed CeO2 and Ga2O3 raw materials in step 1 and mixed evenly, and then subjected to secondary ball milling with alcohol and zirconium balls. The mass ratio of the mixture, alcohol and zirconium balls is 1:1-2:1.5-2, and the ball milling time is 5-10 hours. After ball milling, the obtained slurry is dried at 80°C to obtain secondary ball milling dried powder. Step 6: Granulation. Deionized water and a polyvinyl alcohol solution with a concentration of 5% to 7% are added to the secondary ball-milled dried powder obtained in step 5 and mixed evenly. The mass ratio of the powder, deionized water and polyvinyl alcohol solution is 1:1 to 2:0.15 to 0.

3. After mixing evenly, a spray granulation device is used to spray granulate the obtained mixed slurry to obtain a dry powder. Step 7: Molding: The dry powder obtained in step 6 is placed in a mold and dry-pressed to obtain a green body. Step 8: Sintering: The green body obtained in step 7 is sintered at a temperature of 1500° C. to 1600° C. in an air atmosphere for 4 to 10 hours to obtain a final resonator device.

Citation Information

Patent Citations

  • Novel composite conductive ceramic and method for producing the same

    CN101429021A

  • (SrCa)TiO3-LaAlO3-based microwave dielectric ceramic material and preparation method thereof

    CN103601487A

  • Intermediate high-Q-value microwave dielectric ceramic and preparation method thereof

    CN113956033A

  • (Sr, Ca) (Ti, Ga) O3-LaAlO3 composite microwave dielectric ceramic material and preparation method thereof

    CN115108825A

  • Dielectric microwave dielectric ceramic material with adjustable temperature and drift and preparation method thereof

    CN118479872A